2011
DOI: 10.1007/s11547-011-0734-1
|View full text |Cite
|
Sign up to set email alerts
|

H1N1 pneumonia: our experience in 50 patients with a severe clinical course of novel swine-origin influenza A (H1N1) virus (S-OIV)

Abstract: The most common CXR and CT findings in patients with S-OIV infection were unilateral or bilateral ground-glass opacities with or without associated focal or multifocal areas of consolidation. On MDCT, ground-glass opacities and areas of consolidation had a predominant peribronchovascular and subpleural distribution, resembling organising pneumonia; they progressed to bilateral extensive airspace disease in severely ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…Autopsies show that diffuse alveolar damage, intra-alveolar edema and cellular infiltration are some of the major histopathological findings [2,3842], which are consistent with the findings in this study. Excessive infiltration of immune cells and injury to the lung parenchyma can compromise gaseous exchange by reducing lung volume and compliance [43].…”
Section: Discussionsupporting
confidence: 91%
“…Autopsies show that diffuse alveolar damage, intra-alveolar edema and cellular infiltration are some of the major histopathological findings [2,3842], which are consistent with the findings in this study. Excessive infiltration of immune cells and injury to the lung parenchyma can compromise gaseous exchange by reducing lung volume and compliance [43].…”
Section: Discussionsupporting
confidence: 91%
“…D. A scan obtained at d 97 of illness showed residual subpleural fibrosis in both lower lung lobes. possibly with superimposed secondary bacterial infection at its progressive stage [17]. In our study, superimposed bacterial or fungal infection of the respiratory tract was observed in 3 patients.…”
Section: Discussionsupporting
confidence: 45%
“…Generally, the lung findings first appeared in the lower zones and then rapidly progressed to the middle and upper zones, and the patchy areas progressed to consolidation. Valente et al (21) reported the reversed halo sign for the first time in H1N1 pneumonia. The reports related to the radiological findings of novel influenza A (H1N1) in children are fewer, but most children demonstrated almost similar radiological findings observed in adults (3-7).…”
Section: Discussionmentioning
confidence: 94%
“…In the study of Teplisky et al (5), which included only CXR examinations in 47 patients, consolidation and GGO had a significantly higher frequency in patients who needed more days of oxygen supplement, and initial CXR with lobar consolidation was observed in patients with a greater risk of intensive care unit admission. Valente et al (21) reported 50 patients with a severe clinical course of novel swine-origin influenza A (H1N1) virus (S-OIV) and found that lesion extent is related to aggressiveness of the illness and that the clinical course is worse in obese patients and that superinfection leads to worsening of clinical conditions. Lopez Delgado et al (25) found thrombocytopenia as a mortality risk factor.…”
Section: Discussionmentioning
confidence: 99%